Primary Leptomeningeal Gliomatosis in Children and Adults: A Morphological and Molecular Comparative Study With Literature Review. Issue 3 (March 2016) - Tauziede-Espariat, Arnault; Maues de Paula, Andre; Pages, Melanie; Laquerriere, Annie; Caietta, Emilie; Delpont, Benoit; Viennet, Gabriel; Medeiros de Bustos, Elisabeth; Moulin, Thierry; Barnerias, Christine; Vauleon, Elodie; Grill, Jacques; et al.
Abstract : BACKGROUND: Primary leptomeningeal gliomatosis (PLG) is a poorly recognized tumor of the central nervous system. OBJECTIVE: To describe the histopathological, immunohistochemical, and molecular features of PLG. METHODS: Results of our multicentric retrospective study of 6 PLG cases (3 pediatric and 3 adult) were compared with literature data. RESULTS: The mean age was 54.7 years for adults and 8.7 years for children, with 3 males and 3 females. Clinical symptoms were nonspecific. Cerebrospinal fluid analyses showed a high protein level often associated with pleocytosis but without neoplastic cells. On neuroimaging, diffuse leptomeningeal enhancement and hydrocephalus were observed, except in 1 case. PLG was mostly misinterpreted as infectious or tumoral meningitis. The first biopsy was negative in 50% of cases. Histopathologically, PLG cases corresponded to 1 oligodendroglioma without 1p19q codeletion and 5 astrocytomas without expression of p53. No immunostaining for IDH1R132H and no mutations of IDH1/2 and H3F3A genes were found. Overall survival was highly variable (2-82 months) but seems to be increased in children treated with chemotherapy. CONCLUSION: This study shows the difficulties of PLG diagnosis. The challenge is to achieve an early biopsy to establish a diagnosis and to begin a treatment, but the prognosis remains poor. PLG seems to have a different molecular and immunohistochemical pattern compared with intraparenchymal malignant gliomas. ABBREVIATIONS: OS, overall survival PLG, primary leptomeningeal gliomatosis